2018
DOI: 10.32734/abdimastalenta.v3i1.2354
|View full text |Cite
|
Sign up to set email alerts
|

Kebutuhan Perawatan Gigi Pada Anak Berkebutuhan Khusus Di Sekolah Luar Biasa Taman Pendidikan Islam Medan

Abstract: Children with Special Needs  is a person who has behavioral, physical and intellectual barriers that make doctor have to change approach with various ways to do the treatment.  Children with special needs is a high-risk group for health problems, especially dental caries and periodontal disease, but in fact they are often too late to get dental treatment or never get the treatment. The purpose of this study was to determine the prevalence and experience of caries and dental care needs in children with special … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
0
3
0
4
Order By: Relevance
“…Rendahnya pengetahuan tentang cara memelihara kesehatan gigi dan mulut yang dimiliki, menyebabkan anak berkebutuhan khusus berisiko memiliki masalah kesehatan gigi dan mulut. Anak berkebutuhan khusus adalah anak yang memiliki risiko tinggi terhadap masalah kesehatan, sehingga perlu adanya bantuan dan kerjasama dengan orang lain agar mampu memelihara kesehatannya, termasuk dalam memelihara kesehatan gigi dan mulutnya (Octiara, dkk., 2018).…”
Section: Pendahuluanunclassified
“…Rendahnya pengetahuan tentang cara memelihara kesehatan gigi dan mulut yang dimiliki, menyebabkan anak berkebutuhan khusus berisiko memiliki masalah kesehatan gigi dan mulut. Anak berkebutuhan khusus adalah anak yang memiliki risiko tinggi terhadap masalah kesehatan, sehingga perlu adanya bantuan dan kerjasama dengan orang lain agar mampu memelihara kesehatannya, termasuk dalam memelihara kesehatan gigi dan mulutnya (Octiara, dkk., 2018).…”
Section: Pendahuluanunclassified
“…Berdasarkan hasil Riset Kesehatan Dasar (RISKESDAS) 2018, sebanyak 93% anak di Indonesia mengalami karies gigi [4]. Prevalensi karies gigi pada anak dengan disabilitas yaitu sebesar 92,7% [5]. Tingginya prevalensi karies gigi dapat menimbulkan fungsi penguyahan dalam rongga mulut berlangsung tidak optimal, sedangkan masa anak-anak merupakan masa tumbuh kembang yang memerlukan tingkat kesehatan gigi dan mulut yang optimal.…”
Section: Pendahuluanunclassified
“…Tingginya prevalensi karies gigi dapat menimbulkan fungsi penguyahan dalam rongga mulut berlangsung tidak optimal, sedangkan masa anak-anak merupakan masa tumbuh kembang yang memerlukan tingkat kesehatan gigi dan mulut yang optimal. Oleh karena itu diperlukan upaya promotif dan preventif kesehatan gigi pada anak usia sekolah dasar agar prevalensi karies gigi pada usia dini dapat ditekan bahkan dieliminir, termasuk anak dengan disabilitas usia sekolah dasar karena mereka pun memiliki hak yang sama [5]. Selain itu, peran orang tua sangatlah penting dalam membantu anak dengan disabilitas memelihara kesehatan gigi dan mulutnya.…”
Section: Pendahuluanunclassified
“…The risk of dental and oral health problems in children with special needs is higher than in ordinary children because they have congenital developmental abnormalities that support the high risk of oral cavity problems in children with special needs. 4 The oral hygiene condition of children with special needs was found that they have more dental caries that were not treated, missing teeth due to caries, periodontal disease, and poor oral hygiene compared to other children. Things that can be done to maintain the dental and oral hygiene of children with special needs are the role of parents and dentists needed to maintain their dental health and treat their oral health problems.…”
Section: Introductionmentioning
confidence: 99%
“…Things that can be done to maintain the dental and oral hygiene of children with special needs are the role of parents and dentists needed to maintain their dental health and treat their oral health problems. [3][4] Dental and oral hygiene plays an important role in our overall health and will affect the quality of life such as speaking, chewing, and aesthetic functions. The average OHI-S of the Indonesian people is 1.46 while the national target for the OHI-S index is ≤ 1.2, this shows that the rate of tooth soft tissue damage is quite high.…”
Section: Introductionmentioning
confidence: 99%